Impact of the Outdoor Mathematical Modelling Model Within Differentiated Learning on Students’ Mathematical Literacy Skills - Safitri Fatima Ningsih; Sofnidar Sofnidar; Dewi Iriani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study was motivated by the low mathematical literacy skills of students at SMP Negeri 17 Batanghari. Based on interview results, this condition occurs because the learning process is still teacher-centered and tends to be conventional, without considering differences in students' readiness and learning characteristics. One way to overcome this is by applying the outdoor modeling mathematics model combined with differentiated learning to accommodate differences in student abilities. This study aims to determine the effect of applying the outdoor modeling mathematics model in differentiated learning on students' mathematical literacy skills. This study uses an experimental design with a Posttest-Only Control Group Design. The research population consisted of all seventh-grade students at SMPN 17 Batanghari, comprising five classes. The research subjects involved three seventh-grade classes selected by simple random sampling. These were experiment class I, which applied the outdoor modeling mathematics model in differentiated learning; experiment class II, which applied the direct instruction model in differentiated learning; and the control class, which applied the direct instruction model. The instruments used in this study were a mathematical ability test, an observation sheet on the implementation of learning by teachers and students, and a posttest in the form of a student mathematical literacy test sheet. All instruments were validated through content validity by experts, namely mathematics education lecturers, to ensure the suitability of the instruments with mathematical literacy indicators and learning objectives. In addition, the test instruments were piloted on students with characteristics similar to the research subjects to obtain empirical validity using Product Moment correlation. The reliability of the test instruments was analyzed using Cronbach's Alpha coefficient so that the test instruments were declared reliable and suitable for use in the study. The analysis method applied was one-way ANOVA, followed by a post hoc Tukey test to process the data obtained. The research findings indicate that the use of the outdoor modeling mathematics model in differentiated learning is better at improving students' mathematical literacy skills, while the direct instruction model in differentiated learning does not show significant results when compared to the direct instruction model. In the three sample classes, the implementation of learning by teachers and students was very good. These findings recommend that mathematics teachers apply the outdoor modeling mathematics model in differentiated learning as an alternative to to improve their mathematical literacy skills.